MODERN PREVENTIVE TECHNOLOGIES OF PSYCHOHYGIENIC CORRECTION OF THE ADAPTATION OPPORTUNITIES OF THE STUDENT YOUTH - Serheta , Ihor (Collection of scientific papers «ΛΌГOΣ», 2023)
Modern university medicine should be focused not only on the introduction of measures to limit the adverse impact of certain factors of educational and extracurricular activities on the health of young people and the use of various health-preserving approaches, but also on the broad integration of the latter directly into the educational process and in the extracurricular time, taking into account the individual physical, psychophysiological and mental properties of the personality of students [1, 2, 3].